Creative Fatherhood and Motherhood in Today's Culture of Childlessness - Vaitoška, Gintautas (Socialinė teorija, empirija, politika ir praktika, 2017)
The demographic crisis of Western society is rooted in what could be called the “eclipse of the value of life”. This phenomenon was deeply analysed by the French philosopher Gabriel Marel, who, referring to various contemporary authors, observed that the disintegration of family life and the rise of childlessness in Western society betray signs not so much of a moral decline, but rather a weakening of the perception of the value, beauty and power of life – analogous to the attempt of contemplating the beauty of the sky through a dimmed glass. The result of this ‘cognitive’ crisis is boredom – France was sick with this ‘metaphysical malady’ already in the 1940s, as observed by Marcel. The need for entertainment with all its industrial ramifications could be seen as an effort to fill this void of meaning and existential emptiness. Still, it cannot compensate the depth and power of the ‘nuptial bond between man and life’ – a fundamental anthropological fact, according to Marcel. Among the reasons for the loss of the ‘poetic’ dimension of life, not the least is the fundamental shift in the scientific paradigm that occurred in the epoch of Renaissance, as observed by Christopher Dawson. Thus, biology has become a field of science alienated from the real, one would say, emotionally important facts of life: such terms, as “reproductive system”, “fertility”, primary and secondary “sexual characteristics”, especially in the realm of everyday consciousness, do not allow that which is called “sex” and “sexuality” to be seen as the entrance into the mystery of life of a tremendousgrandeur. Dawson attributes the loss of the esthetic and moral dimension of science to Avveroism – a distorted interpretation of Aristotle by the Arabic tradition overtaken by the Latins in the 13 th century – an interpretation which “discarded the metaphysical dimension of Aristotle’s philosophy”. Therefore, two steps are necessary for recovering the “colors” of reality. The first is to use the abundant evidenceaccumulated by neuroscientific breakthroughs of the last decades about the all-pervading influence of fertility processes on our masculinity and femininity: the beautiful face, attractiveness, romantic passion and, of course, “sexuality” and “sexiness” are a function of the main fertility hormones in a man’s andwoman’s bodies. The second necessary step could partially be understood from the sentimental paintings of love from the Romantic epoch: the hearts of lovers are pierced by an arrow shot by a Cherub, who is a baby. We say “partially”, because the sentimental mode of the Romantic paintings may not evoke the sense of the depth of life to all viewers; nevertheless, a beautiful bride is not only “sexy”, and even notonly “fertile”, no, she is a gatekeeper to the mystery of life – and death, by extension. She is irresistible to a man because of this power; she can relax about her need to fit the stringent body standards of a sexualized culture – as her power over life is of much greater importance over attractiveness (“sexiness”), given she understands it. On the other hand, she can bear fruits of this blossoming only if she avoids the question, as Marcel observed, societies give themselves at the time of ebbing of life: Should I have children? Of course, she has the power to answer in the negative – but, in doing so, she cuts the knot between herself and Life and becomes a powerless toy in the hands of man. Equally so, a man who asks himself, Should I have children?is failing the test of life, says Marcel. This reverence to life must be qualified in order not to be confused with what is sometimes called “providentialism” – the duty to have as many children as one can. But a stringent calculation impoverishes: as a man or a woman denounce their masculine and feminine identity as if it were only a “biological” reality, they also fail – to put it in the words of Erik Erikson – to become generative inthe broadest sense of the word, which happens to be the main condition of a fulfilling life.